Coronary Revascularization in Women - Lundberg, Gina (Clin Cardiol, 2012)
Historically, mortality rates have been higher in women than in men for both PCI and CABG. Recent registries and studies have shown that women have mortality rates similar to men after correcting for age and comorbidities. The gender gap is narrowing with respect to outcomes for women with both PCI and CABG. Revascularization with PCI and CABG in women with stable angina (SA), unstable angina (UA), non ST‐elevation myocardial infarction (NSTEMI), and ST‐elevation myocardial infarction (STEMI) will all be reviewed in light of the most recent studies and registries. © 2012 Wiley Periodicals, Inc. All American College of Cardiology Foundation/American Heart Association guidelines are published in the Journal of the American College of Cardiology and Circulation, and are available online at www.cardiosource.com and http://my.americanheart.org/professional/Statements Guidelines. The authors have no funding, financial relationships, or conflicts of interest to disclose.